Emilia Pardo Bazán, Cuentos fantásticos, ed. Ana Abello Verano y Raquel de la Varga Llamazares, Eolas, León, 2020. - Andrés Sánchez Martínez (Universitat Autònoma de Barcelona, 2020)
Emilia Pardo Bazán, Cuentos fantásticos, ed. Ana Abello Verano y Raquel de la Varga Llamazares, Eolas, León, 2020.